Implementing CD Copyright Protection by Using TCPA Framework - Mohd. Hussin, Nurashikin (Universiti Teknologi Petronas, 2005)
The main objective of this research is to study the current issue of the copyright protection behind the music and software industry. The study also propose a protecting mechanism of commercial audio CDs and software in order to reduce the number of unauthorized duplication of the CDs by consumer. Currently, the music and software industry is facing the piracy problem. This issue is getting bigger from time to time. Therefore, this research will be focusing on current copyright issue, preventing method by using trusted computing framework, TCPA. In developing the project, the research procedures being taken by the author are observation where the author figures out the broad problem area ofthe research, followed by preliminary data investigation and problem definition. The next phase is data collection, analysis and interpretation, and also report writing. The last two phases are the development phase and report and project presentation phase. Meanwhile, the author discusses about findings gathered through out this research. The end product of this research is the concept ofhow TCPA can be implemented in protecting the copyright of the CDsand also the simulation demo authored in Java. The simulation will demonstrate the action taken byCPU in handling CD.